RETRACTED: Calculation of the water flow rate of Micro HPP depending on the water fall angle in ideal cases - Salomov Uktam; Abduraxmonov Sultonali; Urishev Omadjon; Juraev Nurmakhamad (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001